Nurse following robot: An automated robust control nurse following robot with self leveling platform, special wheel, suspension system and sensor integration for crowded hospital ward. - Bukhari, Ilias; Abdul Hamid, Adom, Prof. Madya Dr.; Sazali, Yaacob, Prof. Dr.; Ramachandran, Nagarajan, Prof. Dr.; Khaled, Helmy, Dr. (Malaysian Invention and Design Society (MINDS), 2012)
Bukhari Ilias and his team from School of Mechatronic Engineering won silver for Nurse following robot: An automated robust control nurse following robot with self leveling platform, special wheel, suspension system and sensor integration for crowded hospital ward. 23rd International Invention, Innovation and Technology Exhibition 2012 (ITEX 2012) organized by Malaysian Invention and Design Society (MINDS), 17th - 19th May 2012 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.